Design enhancement of an Oscillating water column for harnessing of wave energy - Abbasi, S.S. (Asian Research Publishing Network, 2017)
Renewable energy resources are in increased demand due to environmental and economic problems associated with the conventional energy resources like fossil fuels. In the past few decades, different ideas, designs and devices have been put forward to extract energy from sea waves. Oscillating water column (OWC) technology is one of these new tools being adopted for wave energy extraction. An OWC device converts wave energy into electricity using high speed air flow caused by fluctuations in water level induced by incoming sea waves. This paper briefly describes two main components of an OWC i.e. air chamber and power take off system. The air chamber, being the major component in energy conversion process, holds significant importance in research studies. Geometric components of an OWC chamber affecting the efficiency of an OWC are also discussed. Although studies have been done on improvement of air chamber designs; however, very few researchers have explored OWC applications under mild sea waves. This paper also addresses development of an OWC with a modified design with reference to the guidelines stipulated by previous researchers. It is anticipated that the proposed OWC model will have better energy extraction performance in the low wave energy climates. © 2006-2017 Asian Research Publishing Network (ARPN).